2019
DOI: 10.1021/acs.nanolett.9b04012
|View full text |Cite
|
Sign up to set email alerts
|

Sheddable Prodrug Vesicles Combating Adaptive Immune Resistance for Improved Photodynamic Immunotherapy of Cancer

Abstract: Photodynamic therapy (PDT) capable of eliciting a robust antitumor immune response has been considered an attractive therapeutic approach. However, adaptive immune resistance in PDT underlines the need to develop alternative strategies. The exquisite power of checkpoint blockade can be harnessed to reinvigorate antitumor immune response. Here, we demonstrate that PDT-triggered adaptive immune resistance can be overcome by inactivating indoleamine 2,3-dioxygenase 1 (IDO-1). We rationally designed a tumor-microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
123
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 181 publications
(125 citation statements)
references
References 34 publications
0
123
0
2
Order By: Relevance
“…In recent years, nanomedicine prepared by using polymers as a carrier has attracted widespread attention . Polymer nanomedicine can be used to improve the solubility of insoluble drugs, prepare sustained‐release preparations with long circulation time, prepare targeted drugs with high efficacy and load biological macromolecules . There are three main methods for preparing polymer nanomedicine: chemical bonding method, polyion complex method and physical encapsulation method.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…In recent years, nanomedicine prepared by using polymers as a carrier has attracted widespread attention . Polymer nanomedicine can be used to improve the solubility of insoluble drugs, prepare sustained‐release preparations with long circulation time, prepare targeted drugs with high efficacy and load biological macromolecules . There are three main methods for preparing polymer nanomedicine: chemical bonding method, polyion complex method and physical encapsulation method.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[18b,34,48] Gao et al designed a matrix metalloproteinase-2 (MMP-2)/ GSH-activatable prodrug vesicle (EAPV) to deliver a PEGylated photosensitizer (PPa) and a reduction-sensitive prodrug IDO-1 inhibitor (NLG919) for photo-immunometabolic cancer therapy ( Figure 5a). [49] The PEGylated PPa was synthesized by conjugating PPa to a PEG chain via an MMP-2-cleavable peptide (GPLGLAG), and the NLG919 prodrug was prepared by coupling In vitro HPPH and IND release in PBS buffer (pH 7.4) and HAc/NaAc buffer (pH 5.0). c) IDO expression and P-S6K activation in IFN-γ-stimulated B16F10 cells after treatment with different IND formulations.…”
Section: Multiple Stimuli-activatable Photo-immunometabolic Therapymentioning
confidence: 99%
“…Gao et al designed a matrix metalloproteinase‐2 (MMP‐2)/GSH‐activatable prodrug vesicle (EAPV) to deliver a PEGylated photosensitizer (PPa) and a reduction‐sensitive prodrug IDO‐1 inhibitor (NLG919) for photo‐immunometabolic cancer therapy ( Figure a). [ 49 ] The PEGylated PPa was synthesized by conjugating PPa to a PEG chain via an MMP‐2‐cleavable peptide (GPLGLAG), and the NLG919 prodrug was prepared by coupling NLG919 with palmitoyl lyso‐phosphocholine via a GSH‐liable space. EAPV could keep stable to avoid drug leakage during the circulation.…”
Section: Photo‐immunometabolic Therapymentioning
confidence: 99%
“…5,6 On the other hand, the TILs-secreted cytokine IFN-γ would lead to upregulation of endogenous indoleamine 2, 3dioxygenase (IDO), which catalyzed tryptophan (Trp) to kynurenine (Kyn). [7][8][9] While Trp exhaustion would in turn suppress TILs activation, Kyn would promote the intratumoral recruitment of the immunosuppressive regulatory T (T reg ) cells, further worsening the immunosuppressive TME. [10][11][12][13] Thus, it has been reported that IDO inhibition could overcome immune suppression to enhance antitumor immune responses.…”
Section: Introductionmentioning
confidence: 99%